Research progress of acupoint application therapy based on midnight-noon ebb-flow in the treatment of constipation after lumbar surgery (子午流注择时穴位贴敷改善腰椎术后便秘的研究进展) - WANG Qiujie (王秋洁); WANG Yuanyuan (王媛媛); QING Jingwen (秦婧文); ZHANG Jianmeng (张建萌); GENG Qingwen (耿庆文) (中西医结合护理)
The constipation is a common complication after lumbar surgery. Constipation can be effectively relieved by pharmacologic interventions. However, there are limitations such as drug dependence and adverse effects. The acupoint application therapy based on midnight-noon ebb-flow shows advantages in the treatment of constipation. This paper summarized the current state of acupoint application therapy based on midnight-noon ebb-flow, and provided reference for clinical nursing practice in relief of constipation after lumbar surgery. (术后便秘是腰椎手术后常见的并发症之一, 通过药物干预可以有效缓解便秘症状, 但存在药物依赖、不良反应等局限性。子午流注择时穴位贴敷在改善便秘方面有其特色和优势, 在临床上患者的接受度普遍较高。本研究主要就该疗法改善腰椎术后便秘的应用现状进行总结, 旨在为临床治疗腰椎术后便秘提供可靠参考。)